Marketing telecommunications services : new approaches for a changing environment - Strouse, Karen G. (Artech House telecommunications library., 1999)
With this single resource, you get comprehensive coverage of fundamental marketing concepts, the latest information available on the marketing activities of telecommunications carriers, and valuable discussion of the continuing impact of U.S. telecommunications deregulation.